Decreased Plasma Ascorbate Levels in Stage IV Melanoma Patients - Schleich, T.; Rodemeister, S.; Venturelli, S.; Sinnberg, T.; Garbe, C.; Busch, C. (Metabolism and Nutrition in Oncology, 2013)
It has been reported that cancer patients frequently express low ascorbate (ascorbic acid, vitamin C) blood levels. However, so far this was not shown for melanoma patients.Total ascorbate (TAA) levels were determined in plasma of healthy control individuals (n=31, mean age: 47.3 years, TAA: 64.86 µM) and in 126 melanoma patients (stage I: n=30, mean age: 51 years, TAA: 59.95 µM; stage II: n=30, mean age: 46.8 years, TAA: 58.85 µM; stage III: n=32, mean age: 48.6 years, TAA: 57.27 µM; stage IV: n=34, mean age: 51.1 years, TAA: 47.16 µM). Plasma TAA levels in stage IV patients were significantly reduced by 27.3% when compared to healthy individuals (p=0.0001, t-test). The reduced plasma TAA levels in stage IV patients negatively correlated with increased S100 and lactate dehydrogenase (LDH) levels. Further, plasma TAA levels were determined in additional 9 stage IV patients directly before and 24 h after intravenous polychemotherapy (carboplatin+paclitaxel, n=5) or immunotherapy (ipilimumab, n=4). TAA levels significantly decreased 24 h after therapy (mean TAA before therapy: 48.7 µM; mean TAA after therapy: 43.0 µM; 11.4% reduction, p<0.05, t-test).Ascorbate levels in the plasma of 126 melanoma patients were significantly decreased in the cohort of stage IV patients and were further decreased by polychemo- or immunotherapy in stage IV patients. Considering the importance of adequate ascorbate supply, ascorbate substitution in physiological doses could be considered for late-stage melanoma patients.
Keywords: vitamin C; ascorbic acid; cancer; chemotherapy; ipilimumab; scurvy